Polymer composite based on polystyrene containing GdF₃ nanoparticles - Sytnik, O.U.; Svidlo, O.V.; Zhmurin, P.N. (Functional Materials, 2013)
Polymeric polystyrene-based composites containing GdF₃ nanoparticles stabilized by ammonium dihexadecyldithioposhate and β-styrylphosphonic acid were obtained by radical bulk polymerization. Use of a component β-styrylphosphonic acid, capable of copolymerizing with styrene, as a modifier of GdF₃ surface allows to increase substantially the content of GdF₃ nanoparticles in polystyrene plastic scintillator without changing its scintillations properties.